Tingkat Kebugaran Jasmani Atlet Atletik Remaja di Kota Tangerang: Studi Deskriptif - Perbawanti, Wanda; Nugraha, Reshandi; Sumpena, Asep (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to evaluate the physical fitness level of adolescent track and field athletes aged 13–15 years in Tangerang City. Physical fitness plays an important role in athlete performance, especially in athletics that require speed, strength, endurance, and muscle explosive power. The research method used is a quantitative descriptive approach with a purposive sampling technique. The sample consisted of 35 club athletes and 35 athletes from coaching centers in the area. The instrument used was the Indonesian Physical Fitness Test (TKJI) which includes 50-meter running, hanging body lifting, lying sitting, vertical jump, and middle-distance running (1000 meters for men and 800 meters for women). Data analysis was carried out using the independent sample t-test with SPSS software. The results showed that there were significant differences in two components in each group. In the men's group, significant differences were found in the 50-meter run and 1000-meter run. While in the women's group, significant differences occurred in the vertical jump and 800-meter run. Other components showed similar performance between groups. These results indicate the need for a more specific training approach based on the results of each group's fitness evaluation. These findings not only provide practical contributions in the development of adolescent athletes, but also enrich academic studies on physical fitness during the growth period. Keywords: physical fitness, athletics, rutuyouth athletes.